Zespół obkurczenia torebki soczewki jako przyczyna podwichnięcia implantu wraz z torebką soczewki oraz uproszczona metoda operacyjna repozycji wszczepu - Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Presentation of the case of the pseudophakic patient in whom 3 months after uncomplicated phacoemulsification severe capsule contraction syndrome, followed by equatorial capsule fibrosis, 240 degree zonular dialysis, and spontaneous in-the-bag intraocular lens subluxation, were observed. Consecutive surgical intervention consisting of simplified transscleral „free haptic” through the capsule fixation and additional plastic of phimotic capsulorrhexis allowed to restore the best corrected visual acuity to 20/25.